2021
DOI: 10.3390/su132011243
|View full text |Cite
|
Sign up to set email alerts
|

The New Progression Model of Entrepreneurial Education—Guideline for the Development of an Entrepreneurial University with a Sustainability Approach

Abstract: Entrepreneurship is becoming understood as a set of competencies needed for many professions and, as a result, requires to be integrated into higher education even in such seemingly distant areas as, e.g., public administration, sport, agriculture, tourism, etc. Therefore, there is a need for research-based guidance on how to introduce and develop entrepreneurial education as an enabling approach to the transition in higher education that could serve as an integral part of a paradigm shift towards an entrepren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…In this system, general education courses are used to cultivate innovative interests, specialized courses are used to develop innovative knowledge and abilities, and selflearning courses are used to promote innovative practical abilities [7] . The three types of courses are set up in a crisscross manner, establishing a new intra-curriculum design mechanism for the education of "integration of expertise and innovation."…”
Section: 1mentioning
confidence: 99%
“…In this system, general education courses are used to cultivate innovative interests, specialized courses are used to develop innovative knowledge and abilities, and selflearning courses are used to promote innovative practical abilities [7] . The three types of courses are set up in a crisscross manner, establishing a new intra-curriculum design mechanism for the education of "integration of expertise and innovation."…”
Section: 1mentioning
confidence: 99%
“…This tendency towards an understanding of entrepreneurship in a broader way and, at the same time, a growing need for inclusion of sustainability issues in education, should consequently lead to the expansion of the entrepreneurial university concept. The postulated expansion of an entrepreneurial university approach creates a new response to some of the concept's criticism about the perceived growing dependency of higher education institutions from the industrial and business partners or sponsors [29]. Entrepreneurship education in entrepreneurial universities increased students' motivation and recommended tutor training with a real-world approach.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In business schools, these include "entrepreneurial education", or systematic preparations of students for careers in industry through courses and practices [12]. Other research suggests the need for a "shift from the main focus from HEIs external stakeholders towards internal stakeholders-educators and students"-in order to create an encompassing entrepreneurial education across multiple disciplines [98]. Certain studies have suggested that to truly foster IAC, HEIs should establish "science-based entrepreneurship education" to foster TT and truly embed industry in science, and vice versa [9]; this type of education is also closely related to interdisciplinarity.…”
Section: Involving Students In Interdisciplinary Research and Industr...mentioning
confidence: 99%